THE EFFECT OF LOVE OF MONEY, TAX SYSTEM, AND JUSTICE ON TAX EVASION - Lukman Lukman; Yakobus Kaditti Bangun; Michelle Phing Phing Fajar Philips (SIMAK, 2023)
This study aims to examine the effect of love of money, taxation system, and tax justice on tax evasion. The case study in this research is located at KPP Pratama Makassar Barat. The population in this study is an individual taxpayer registered with the KPP Pratama Makassar Barat in 2020. The sampling technique in this study used purposive sampling with a sample of 100 respondents. Research data sourced from questionnaires distributed to taxpayers at KPP Pratama Makassar Barat. The data analysis method used is multiple linear regression analysis, while the data processing uses SPSS 25. The results showed that love of money has a positive and significant effect on tax evasion, which means that the higher a person's love for money (love of money), the higher the tax evasion that occurs. The tax system has a positive and significant effect on tax evasion, which means that the worse the tax system applied, the higher the cases of tax evasion that occur. Justice has a positive and significant effect on tax evasion, which means the lower the justice that occurs, the higher the tax evasion cases that occur.